2020
DOI: 10.1186/s12950-020-00258-0
|View full text |Cite
|
Sign up to set email alerts
|

Compound amino acid combined with high-dose vitamin B6 attenuate traumatic coagulopathy via inhibiting inflammation by HMGB1/TLR4/NF-κB pathway

Abstract: Background: Traumatic coagulopathy (TC) arises primarily from coagulation system failure to maintain adequate hemostasis after serious blood loss or trauma. Circulatory homeostasis restoration is the mainstay of the therapeutic approach to TC, but the effects are significantly inhibited by coagulopathy. Objective: To identify the therapeutic effects and underlying mechanism of compound amino acid (CAA) combined with high-dosage of vitamin B6 (VB6) on TC. Methods: Rabbit traumatic model and cellular model were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…53 On the other hand, vitamin B6 exerted anti-inflammatory effects by inhibiting the TLR4/NF-κB signaling pathway. 54 Thus, our results in metabolomics and transcriptomics collectively suggest that EGPH might relieve DSS+HFDinduced NAFLD by increasing hepatic vitamin B6 levels, which can activate or inhibit the PPAR and TLR4/NF-κB signaling pathways.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…53 On the other hand, vitamin B6 exerted anti-inflammatory effects by inhibiting the TLR4/NF-κB signaling pathway. 54 Thus, our results in metabolomics and transcriptomics collectively suggest that EGPH might relieve DSS+HFDinduced NAFLD by increasing hepatic vitamin B6 levels, which can activate or inhibit the PPAR and TLR4/NF-κB signaling pathways.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…Activation of PPAR-α also alleviated mitochondrial dysfunction induced by HFD through the FGF21-AMPK-PGC-1α pathway, thereby preventing cell damage caused by steatosis. , Meanwhile, vitamin B6 could down-regulate the expression of hepatic PPAR-γ protein in hyperlipidemic rats . On the other hand, vitamin B6 exerted anti-inflammatory effects by inhibiting the TLR4/NF-κB signaling pathway . Thus, our results in metabolomics and transcriptomics collectively suggest that EGPH might relieve DSS+HFD-induced NAFLD by increasing hepatic vitamin B6 levels, which can activate or inhibit the PPAR and TLR4/NF-κB signaling pathways.…”
Section: Resultsmentioning
confidence: 63%
“…Vitamin B6 was also found to protect mice from toxic effects induced by LPS by preventing IL-1Β protein production via the inhibition of NLRP3 inflammasome activation [ 106 ] and also inhibits activation of NF-κB in LPS-stimulated mouse macrophages [ 107 ]. Furthermore, high-dose B6 combined with compound amino acid was shown to prevent inflammation by inhibiting the HMNGB1/TLR4/NF-κB signalling pathway [ 108 ]. Interestingly, we note that vitamin B6 significantly downregulated NF-κB IL-6 , IL-1β , TNF-α , and NLPR3 , which aligns with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in regulating immunity and inflammation via controlling production of inflammatory cytokines (Stach et al, 2021). Recently, Yi et al (2020) indicated that vitamin B6 suppressed the expression of inflammatory cytokines , IL-1β, and tumor necrosis factor-α (TNF-α)] in rabbits. Liu et al (2018) evidenced that dietary supplementation of vitamin B6 (0, 5, 10, 20, and 40 mg/kg) increased BWG and FI and reduced the diarrhea ratio in weaned Rex rabbits.…”
Section: Vitamin B6mentioning
confidence: 99%